A NIR fluorescent probe for the detection and visualization of hydrogen sulfide using the aldehyde group assisted thiolysis of dinitrophenyl ether strategy. Issue 47 (14th November 2018) - Qian, Ming; Zhang, Liuwei; Pu, Zhongji; Xia, Jing; Chen, Lili; Xia, Ying; Cui, Hongyan; Wang, Jingyun; Peng, Xiaojun
Abstract : A NIR fluorescent probe exploiting the aldehyde group assisted thiolysis of dinitrophenyl ether strategy for H2 S imaging in cells, tissues and mice. Abstract : In view of the significant physiological and pathological roles H2 S plays in living systems, it is crucial to develop fluorescent probes for H2 S detection with high sensitivity and good selectivity. Herein, a novel NIR fluorescent probe NDCM-2 based on the dicyanoisophorone derivative was designed and synthesized by employing ortho -aldehyde assisted thiolysis of 2, 4-dinitrophenyl (DNP) ether as the sensing strategy to achieve highly specific H2 S detection in living systems. The studies demonstrated that probe NDCM-2 exhibited excellent sensing performance toward H2 S with 160-fold NIR fluorescence enhancement, a rapid response within 15 min, excellent sensitivity with a detection limit of 58.797 nM, a large Stokes shift of 170 nm and good selectivity. In light of these unique properties, NDCM-2 has been successfully applied for the fluorescence imaging of H2 S in biological systems (living cells, tissues and mice), demonstrating that it would be an effective tool for H2 S detection in living systems.